Legal Risks in Employee Relations: Legal Considerations in Human Resource Risk Management - Maslan, Jhoni; Jamaludin, Maun (JURNAL AKTA, 2024)
This paper explores the critical legal considerations that organizations must address when managing Human Resources (HR) risks. Effective HR risk management involves aligning employee management practices with legal frameworks to minimize liabilities and protect both employees and employers. By examining key legal areas such as employment contracts, workplace safety, anti-discrimination laws, privacy regulations, and labor unions, this paper demonstrates how legal compliance impacts HR decision-making and employee performance. Through an analysis of case law and organizational strategies, the paper highlights the essential role of HR professionals in mitigating legal risks and creating a legally sound workplace. Recommendations for improving HR risk management practices in compliance with labor laws are also provided.